Changes of condensed tannins during decomposition of leaves of Kandelia obovata in a subtropical mangrove swamp in China - Zhou, Hai-Chao; Tam, Nora Fung-yee; Lin, Yi-Ming; Wei, Shu-Dong; Li, Yuan-Yue; 林益明 (SOIL BIOL BIOCHEM, 2012)
National Eleventh Five-Year Key Project; National Natural Science Foundation of China; Program for New Century Excellent Talents in University Kandelia obovata, with abundant condensed tannins (CTs), is a typical mangrove species in China, but little is known about the chemical alterations and ecological roles of CTs during leaf litter decomposition. A litterbag experiment was conducted to investigate the changes of CTs in a subtropical mangrove swamp along Zhangjiang River Estuary, China, using the colorimetric assays, reversed/normal-phase HPLC-ESI-MS and MALDI-TOF-MS techniques. Total phenolics (TP), extractable CTs (ECT) and total CTs (TCT) decreased rapidly, while bound CTs (BCT), including protein- and fibre-bound CTs in leaves, increased during decomposition, and these temporal changes were well-expressed by exponential functions. Negative correlations between nitrogen (N) and TP, as well as N and ECT were found; however, a positive correlation between N and BCT was detected, suggesting that CTs played an important role in humification during N immobilization. The HPLC-ESI-MS analyses showed that the polymerization degree of CTs had an initial increase, due to leaching, followed by a decrease in the subsequent shift towards abiotic or/and biotic degradation. MALDI-TOF-MS confirmed the degradation processes for CTs. A decrease in the degree of hydroxylation, along with an increase in glycosylation-CTs, was obtained during litter decomposition. These chemical changes enhanced the current knowledge on the potential ecological role of N transformation in CTs in mangrove swamps. (C) 2011 Elsevier Ltd. All rights reserved.